Anti-inflammatory effects of gastrointestinal digested Sambucus nigra L. fruit extract analysed in co-cultured intestinal epithelial cells and lipopolysaccharide-stimulated macrophages. (December 2015) - Olejnik, Anna; Kowalska, Katarzyna; Olkowicz, Mariola; Rychlik, Joanna; Juzwa, Wojciech; Myszka, Kamila; Dembczyński, Radosław; Białas, Wojciech
Highlights: Peonidin-3-sambubioside and peonidin-3-glucoside were identified in elderberries. Excessive ROS generation was reduced by gastrointestinal digested elderberries. Digested extract showed anti-inflammatory capacity following intestinal absorption. Gastrointestinal modified extract down-regulates proinflammatory genes expression. Abstract: In order to evaluate potential therapeutic properties of Sambucus nigra fruit extract, its anti-inflammatory effects were investigated in lipopolysaccharide-activated RAW264.7 macrophages. Physiochemical changes in the extract composition, which occur following oral administration, were mimicked in an artificial alimentary tract, while transepithelial absorption was simulated using enterocyte-like Caco-2 cell monolayer, imitating intestinal barrier. The obtained results showed that gastrointestinal digested extract, transported across intestinal epithelium, down-regulated the expression of major genes of inflammatory pathway, such as IL-1β, IL-6, TNF-α and COX-2. Reduction of IL-6, TNF-α and prostaglandin E2 secretion was also observed as a result of LPS-stimulated macrophages' treatment. Moreover, enhanced nitric oxide production in response to inflammatory stimuli in RAW264.7 cells was controlled by the digested and intestinal permeable fraction of elderberry extract.